Ficus minahassae (Teijsm. & de Vriese) Miq.: A Fig Full of Health Benefits from North Sulawesi, Indonesia: A Mini Review - Abas, Abdul Hawil; Tallei, Trina Ekawati; Idroes, Rinaldi; Fatimawali, Fatimawali (Malacca Pharmaceutics, 2023)
Plants have been widely utilized as traditional medicine for an extended period of time. Numerous traditional remedies have demonstrated inherent anti-disease properties. Among the countries that extensively rely on traditional medicine, Indonesia stands out. Within the region of North Sulawesi, Indonesia, Ficus minahassae, an indigenous plant possessing several health benefits, is utilized by the local community as a traditional medicinal resource. This plant is employed for the treatment of various ailments such as rheumatism, physical discomfort, stimulation of lactation in breastfeeding women, bruises, relapse, fever, fatigue, migraines, bodily pain, headaches, convulsions, colds, coughs, influenza, and fractures. Typically, the leaves, roots, and stems of F. minahassae are boiled and consumed. Additionally, this plant has been reported to possess antibacterial and antioxidant properties. However, scientific investigations exploring the health advantages of F. minahassae are significantly limited in comparison to other traditional medicines. Consequently, it is highly recommended to conduct further research on the health benefits associated with this plant.